2000
DOI: 10.1128/jcm.38.11.4010-4014.2000
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Highly Sensitive and Specific Enzyme-Linked Immunosorbent Assay Based on Recombinant Matrix Protein for Detection of Avian Pneumovirus Antibodies

Abstract: The matrix (M) protein of avian pneumovirus (APV) was evaluated for its antigenicity and reliability in an enzyme-linked immunosorbent assay (ELISA) for diagnosis of APV infection, a newly emergent disease of turkeys in United States. Sera from APV-infected turkeys consistently contained antibodies to a 30-kDa protein (M protein). An ELISA based on recombinant M protein generated in Escherichia coli was compared with the routine APV ELISA that utilizes inactivated virus as antigen. Of 34 experimentally infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Until now, serological assays for hMPV have used infected cells as the antigen and none have been developed based on a recombinant protein (2,9,10,12,24,29). It has been demonstrated that recombinant protein ELISAs were more sensitive than those using virus-infected cells or inactivated virus as the antigen for detecting aMPV antibodies (15,16). Among the hMPV proteins, the nucleoprotein (N) along with the matrix (M) and the fusion (F) proteins are the most conserved between representatives of the two hMPV groups (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, serological assays for hMPV have used infected cells as the antigen and none have been developed based on a recombinant protein (2,9,10,12,24,29). It has been demonstrated that recombinant protein ELISAs were more sensitive than those using virus-infected cells or inactivated virus as the antigen for detecting aMPV antibodies (15,16). Among the hMPV proteins, the nucleoprotein (N) along with the matrix (M) and the fusion (F) proteins are the most conserved between representatives of the two hMPV groups (1).…”
Section: Discussionmentioning
confidence: 99%
“…Serological tests based on an enzyme-linked immunosorbent assay (ELISA) have been developed for the detection of aMPV antibodies. In those assays, different antigens were used, including lysed infected cell culture preparations as well as recombinant viral proteins, such as the matrix protein (M) and the nucleoprotein (N) (7,15,16). Those assays were found to be sensitive and specific for detecting aMPV antibodies, with the recombinant protein-ELISA test being more sensitive than assays using virus-infected Vero cells as the antigen (16).…”
mentioning
confidence: 99%
“…The virus can be isolated from tracheal swabs or turbinates 1-7 days after the onset of clinical signs (Gulati et al, 2000). In Europe, APV has been propagated in embryo tracheal organ cultures from chickens and turkeys, and in the USA APV has been isolated in chicken embryo fibroblasts and then adapted to Vero cells.…”
Section: Virus Isolationmentioning
confidence: 99%
“…Cytopathic effects in Vero cells are observed 2-3 days after inoculation. Virus isolation is time-consuming and insensitive when used as a diagnostic tool, and virus cannot be isolated from samples obtained at an advanced stage of clinical disease (Gulati et al, 2000). For example, APV was isolated in only 11% of samples collected from naturally infected commercial turkeys showing overt clinical signs of APV, whereas 88.4% of the samples were positive by ELISA (Gulati et al, 2000).…”
Section: Virus Isolationmentioning
confidence: 99%
“…It is the most immunogenic and protective viral antigen, evoking a strong antibody response and acting as a major target for cytotoxic T cells (Collins et al., 2001). Several reports showed that the APV subgroups A, B and D were more closely related to each other than each was to subgroup C (Gulati et al., 2000; Toquin et al., 2000; Shin et al., 2002). Surprisingly, APV/C showed the closest resemblance to the newly discovered human metapneumovirus (hMPV), with amino acid identities for the N, P, M and F proteins ranging from 66% to 89% (van den Hoogen et al., 2002; Bastien et al., 2003; Lwamba et al., 2005).…”
Section: Introductionmentioning
confidence: 99%